2020
DOI: 10.1042/bsr20200019
|View full text |Cite
|
Sign up to set email alerts
|

Brevinin-1GHd: a novel Hylarana guentheri skin secretion-derived Brevinin-1 type peptide with antimicrobial and anticancer therapeutic potential

Abstract: Host-defense antimicrobial peptides (AMPs) from amphibians are usually considered as one of the most promising next-generation antibiotics because of their excellent antimicrobial properties and low cytotoxicity. In the present study, one novel Brevinin-1 type peptide, Brevinin-1GHd, was isolated and characterized from the skin secretion of the frog, Hylarana guentheri. Brevinin-1GHd was found to possess a wide range of antimicrobial activity through penetrating the bacterial membrane within a short time while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…Dermaseptin-PS1 inhibits human glioblastoma U-251 MG cells (from cells frozen in Uppsala in 1969) via inducing apoptosis at a low micromolar concentration and disrupts cancer cell membranes at 10-fold the concentration [ 112 ]. Moreover, brevinin-1GHd was shown to inhibit proliferation of human cancer lines [ 113 ]. As a means to improve cell selectivity of anticancer peptides, some compounds may be utilized to potentiate peptide potency [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dermaseptin-PS1 inhibits human glioblastoma U-251 MG cells (from cells frozen in Uppsala in 1969) via inducing apoptosis at a low micromolar concentration and disrupts cancer cell membranes at 10-fold the concentration [ 112 ]. Moreover, brevinin-1GHd was shown to inhibit proliferation of human cancer lines [ 113 ]. As a means to improve cell selectivity of anticancer peptides, some compounds may be utilized to potentiate peptide potency [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…AMPs have been recognized as the first line of defense against pathogens infection, and a growing body of evidence suggested that some AMPs showed anticancer and antiviral activities (Jiang et al 2020 ). In the present study, LHH1 was a novel AMP that identified from the genome of L. casei HZ1 with potent antibacterial effect on S. aureus and anticancer potency on several cancer cells (Table 3 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AMPs have been recognized as the rst line of defence against pathogens infection, and a growing body of evidence suggested that some bactericidal peptides showed anticancer and antiviral activities (Jiang et al 2020). In the present study, LHH1 was a novel AMP that identi ed from the genome of L. casei HZ1 with potent bactericidal effect on S. aureus and anticancer potency on several cancer cells (Table 3 and Fig.…”
Section: Discussionmentioning
confidence: 65%